Sistem Monitoring Nutrisi dan PH Air pada Tanaman Hidroponik Berbasis Internet of Things (IoT) - Rivana, Rivana Risqi; Made, Made Rahmawaty; Edilla; Jajang Jaenudin (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2023)
Hydroponics is a soilless cultivation method that relies on water and the fulfillment of plant nutritional needs. Nutrient provision is usually done manually, which can be time-consuming. To improve efficiency, an automated system using sensors and an IoT-based application can be implemented. This system utilizes a TDS sensor, pH sensor, and NodeMCU ESP32 to monitor nutrient and pH levels in water. The values are displayed on an LCD screen and sent to the application. If the nutrient content falls below 700 ppm or the pH falls below 5 or above 8, indicating a nutrient deficiency, the nutrient pump can be remotely activated through the application. The pump stops when the nutrient level reaches 1000 ppm or the pH reaches 8. The system provides TDS and pH readings, which have an average error of 3.16% and 2.87%, respectively. This automated system can be used to reading TDS and pH values to assist in providing nutrients to hydroponic plants.